Comparing sensibility for touch, cold, and warmth in different skin areas. (2nd April 2016) - de Rezende Strander, Nanna; Ståhle, Lars; Hansson, Per T.
Abstract: The primary objective of this pilot study was to assess if the magnitude estimation of suprathreshold brushing, warmth (40 °C), and cold (25 °C) stimuli of the skin over the dorsum of the hand and the dorsum of the foot are comparable to the perceived intensity for the same stimuli applied to the skin over any of the following areas: forehead, m. trapezius, m. deltoideus, thoracic back, and lumbar back, respectively. Thirty-two subjects aged 18–64 years were included. Participants were examined by two physicians on two different occasions, 1–58 days apart. Participants rated the magnitude of the perceived sensation of each stimulus on an 11-point numerical rating scale (NRS) 0–10, where 0 was anchored to "no sensation at all for touch/cold/warmth" and 10 anchored to "the most intense imaginable non-painful sensation of touch/cold/warmth". The criterion for sensory equivalence for one modality was arbitrarily considered satisfactory if two regions had the same numerical rating ±1 point in at least 85% of the individuals. Based on the pre-study criteria for sensory equivalence applied in this study only one area was found to be equivalent to the foot skin for the percept of brushing, that is, the skin over the deltoid muscle and one area for the hand, that is, the skin over the forehead. We failed to find any area with equivalent sensitivity to the hand or the foot for the cold or warm stimuli.